Aplicação da termografia infravermelho para identificação de desplacamento cerâmico - Melo, Sizy Brenda de (2024)
Structures are subject to the direct action of environmental agents such as humidity and temperature variations. These conditions can strongly influence the degradation of materials and even accelerate it. On building facades, degradation intensifies the infiltration of rainwater and the loss of adhesion of ceramic coverings. Early identification of flaking by visual inspection is still a challenge. The trend observed in literature reports is that infrared thermography is an alternative tool capable of identifying damage to facades in addition to other applications. However, this technique is not yet sufficiently developed and advances are needed for large-scale application. Thermography is a non-destructive test that measures and records the infrared temperature on the surface of a material according to emissivity. Thermograms can be recorded without direct contact with the analyzed surface, therefore, without damaging the structure. The main objective of this research is to characterize the thermal behavior of peeled and well-adhered areas using infrared thermography, considering multi-parameters. To this end, inspections were carried out throughout the day on different coating colors for two times of the year. Image capture distance, temperature, sun position, characteristics of ceramic plates, edge effects and the influence of reflections and shading are discussed. The results indicate that ceramic flakes gain heat faster during the heating phase and dissipate first during the cooling phase. Peelings are easily noticed in dark-colored coatings, while light-colored coatings often suffer from the influence of external factors, especially in rainy seasons. The most accurate times are from 7am to 6pm. Overall, infrared thermography proves to be a potential technique as it presents a considerably high level of assertiveness.